Historical trends in the nitrogen requirement of corn over 45 years in Ohio - Fulford, Anthony M.; Labarge, Gregory; Lindsey, Alexander; Watters, Harold; Ortez, Osler; Culman, Steven W. (Wiley, 2025)
The average annual corn (Zea mays L.) grain yield in Ohio has increased since the 1970s, yet the respective roles of corn hybrids and optimal nitrogen (N) fertilization in contributing to this historical trend remain unclear. This study evaluated trends in the agronomically optimal nitrogen rate (AONR) and corn grain yield at agronomically optimal nitrogen rate (YAONR) when corn followed corn (CC) or soybean [Glycine max (L.) Merr.] (SC) in the crop rotation within two eras of corn hybrid development. The two eras were associated with different technological development phases, including 1976–1995 (pre-transgenic era) and 1996–2021 (transgenic era). A total of 431 rainfed corn fertilizer N rate response trials were conducted in 31 Ohio counties over 45 years. From 1976 to 2021, AONR did not significantly increase, while YAONR increased by 96.1 kg ha−1 year−1, a 52% increase over 45 years. The YAONR significantly increased by 95 kg ha−1 year−1 for CC and 68 kg ha−1 year−1 for SC. Unfertilized (0 kg N ha−1) corn yield gains were similar to annual yield gain at AONR, and the agronomic nitrogen-use efficiency (ANUE) greatly improved over 45 years, with an additional 4.6 kg of grain per kg of N for corn grown in 2021 compared to 1976. Overall, our study demonstrated that historical yield gains were largely due to improved corn hybrid ANUE and management rather than changes in N fertilizer requirements.